Project Management and Engineering : Selected Papers from the 17th International AEIPRO Congress held in Logroño, Spain, in 2013 - Ayuso Muñoz, José Luis; Yagüe Blanco, José Luis; Capuz-Rizo, Salvador F. (Lecture Notes in Management and Industrial Engineering,, 2015)
Project Management and Engineering is an emergent area. Every day more projects have bigger size, more stakeholders involved, more environmental, organizational and technological complexity, and a better degree of fulfilment requirements. The foregoing causes greater demands on the effectiveness of Project Engineering and the efficiency of Project Management. This volume puts together a collection of recent works of researchers and professionals in the Project Management and Engineering fields of Civil Engineering, Environmental Engineering, Energy Efficiency, Rural Development, Production and Process Engineering, Industrial Design and Information Technology and Communication.